International mobility, sexual behaviour and HIV-related characteristics of men who have sex with men residing in Belgium - Vanden Berghe, Wim (BioMed Central, 2013)
BACKGROUND: European men who have sex with men (MSM) continue to be disproportionally affected by the human immunodeficiency virus (HIV). Several factors are contributing to the rates of new HIV infections among MSM. The aim of this study was to investigate the potential role of travel behaviour and sexual mobility in the spread of HIV and sexually transmitted infections (STI) among European MSM. METHODS: Belgian data from the first pan-European MSM internet survey EMIS was used (n=3860) to explore individual and contextual determinants of sexual behaviour among MSM, who resided in Belgium at the time of data collection and who reported having had sexual contact abroad in the last 12 months. Descriptive and bivariate analyses were performed. Odds ratios and 95% confidence intervals were calculated by means of logistic regression. RESULTS: MSM who practiced unprotected anal intercourse UAI during their last sexual encounter abroad were less likely to be living in a large city (OR:0.62, 95% CI:0.45-0,86, p<0.01) and more likely to be HIV positive (OR:6.20, 95% CI:4.23-9.06, p<0.001) ), to have tested HIV positive in the last 12 months (OR:3.07, 95% CI:1.07-8.80, p<0.05), to have been diagnosed with any STI in the last 12 months (OR:2.55; 95% CI:1.77-3.67, p<0.05), to have used party drugs (OR:2.22, 95% CI:1.59-3.09, p<0.001), poppers (OR:1.52, 95% CI:1.07-2.14, p<0.001) and erection enhancing substances (OR:2.23, 95% CI:1.61-3.09, p<0.001) compared to MSM who did not have UAI with their last sexual partner abroad. Men having had UAI in the last 12 months were more likely to have done so in a neighbouring country of Belgium (OR:1.66, 95% CI:1.21-2.29, p<0.001). Different sexual behavioural patterns related to condom use and drug use were identified according to HIV test status among travelling men. CONCLUSIONS: The results of this study provide evidence for the role of international mobility and sexual behavior while travelling, in the spread of HIV and STI among MSM in Europe. Further, the findings underline the need for development of European cross-border HIV and STI interventions with coherent messages and prevention policies for MSM.